The Effect Of Ratcheting Effect On Regional Original Revenue And Regional Expenditure Of Malacca Regency In 2019-2023 - Tkela, Melianus. E; Tefa, Siprianus G.; Bahantwelu, Maria Immaculata (SEAN Institute, 2024)
This study aims to determine the effect of Regional Original Income with Regional Expenditures and the effect of ratcheting on the relationship between PAD and Regional Expenditures in Kab. Malaka. This type of research is a quantitative research and the research approach used is a qualitative approach. The population and sample in this study were Malaka Regency. The types and sources of data used were primary data types and secondary data types. The research variables used in this study were exogenous (Regional Original Income) and endogenous (Racheting Effect) variables. The data collection technique used in this research is the literature study method and the documentation method. The data analysis technique used partial least square (PLS). The data analysis techniques used in testing the hypothesis of this research are as follows: 1) Designing a structural model (Inner Model), 2) Measurement model (Outer Model), 3) estimating, 4) Evaluating the structural model of the construct, 5) Testing hypotheses. The results of this study indicate that Regional Original Income (PAD) has a negative effect on regional spending and the Ratcheting Effect has a positive and significant effect on the relationship between Regional Original Income and Regional Expenditures.